Investigation of the relationship between age groups and feeding of Leuciscus vorax (Aspius vorax ) and their parasitic infection: تقصي علاقة مجاميع عمر وتغذية أسماك الشلق بإصاباتها الطفيلية - AL-Asadiy, Yassir Dakheel (Journal of Kerbala for Agricultural Sciences, 2018)
A total of 194 specimens of Leuciscus vorax (Heckel, 1843) were collected from the Euphrates River passing through Samawa, Al-Sawyer area for the period from 2016 until the end of April 2017 to investigate parasitic infections .The results showed that there were six age groups (II +- VII +) for male and female fish with the dominance of the age group (III+) and that the fish fed on the phytoplankton and crustaceans in small age groups and on fish and insects in large age groups. Crustaceans, fish and insects are the main food groups with a total percentage 66.44 , 29.89 and 13.92 respectively .The results showed that ( 135) fish were infected with a total percentage 69.59. One species was diagnosed,Trichodina pediculus, as well as two species of nematodes Rhabdochona khazirensis and Rhabdochona denudata, Leuciscus vorax is considered a new host record in Iraq of parasites T. pediculus and R. khazirensis, as well as a correlation between the parasites causing this type of infection. The highest value of coefficient of contingency 0.9767 was recorded between R. denudata and ciliated parasite T. pediculus, compared between the value of coefficient of contingency between T. pediculus parasite and R. khazirensis 0.9668,The lowest value of coefficient of contingency between parasite R. denudata and parasite R. khazirensis 0.8666.